Investigations of the Co-Pt alloy phase diagram with neutron diffuse scattering, inverse cluster variation method, and Monte Carlo simulations - Fevre, Mathieu (2020)
The short-range order in a CoPt alloy was determined at 1203 and 1423 K using neutron diffuse scattering measurements. The effective pair interactions provided by data analysis reproduce well the experimental order-disorder transition temperature in Monte Carlo simulations. They complete previous results reported for the Co-Pt system and are compared to those obtained within tight-binding and ab initio formalisms. Our results show that the important dependence of the nearest-neighbor pair interactions with composition is not related to the sample magnetic state at the measured temperatures. Interactions measured in the paramagnetic domain for the CoPt alloy behave like those in the ferromagnetic domain for the Co₃Pt and Co₀․₆₅Pt₀․₃₅ alloys. The effective pair interactions related to the tight-binding Ising model provide a relatively good description of the CoPt alloy thermodynamics close to the ordering temperature (short-range order and temperature of phase transformation), even if they strongly differ from those measured in this study. The average magnetic moment of Co atoms at high temperatures was determined from the analysis of the intensity contribution that is not dependent on the scattering vector. The obtained value is very close to the moment measured at room temperature or determined from ab initio calculations. This confirms the Curie-Weiss behavior of the CoPt alloy. Finally, transmission electron microscope observations carried out on samples annealed for about 30 days confirmed that the order-disorder transition takes place in the 830–843 K temperature interval at the Co₃Pt composition.